A first insight into tuberculosis transmission at the border of Ecuador and Colombia: a retrospective study of the population structure of Mycobacterium tuberculosis in Esmeraldas province - Castro-Rodriguez, Bernardo; Espinoza-Andrade, Sebastián; Franco-Sotomayor, Greta; Benítez-Medina, José Manuel; Jiménez-Pizarro, Natalia; Cárdenas-Franco, Camilo; Granda, Juan Carlos; Jouvin, Jose Luis; Orlando, Solon Alberto; Hermoso de Mendoza, Javier; García-Bereguiain, Miguel Ángel (Frontiers in Public Health, 2024)
Objective. Tuberculosis (TB) is a major public health problem in Ecuador and Colombia, both high burden settings for drug resistance TB. Molecular epidemiology is crucial to understand the transmission dynamics of Mycobacterium tuberculosis Complex (MTBC) and to identify active transmission clusters of regional importance. Methods. We studied the potential transmission of TB between Colombia and Ecuador through the analysis of population structure of MTBC lineages circulating in the Ecuadorian province of Esmeraldas at the border with Colombia. A total number of 105 MTBC strains were characterized by 24-loci MIRU-VNTR and spoligotyping. Results. MTBC lineage 4 is the only present in Esmeraldas; no MTBC strains belonging to Lineage 2-sublineage Beijing were found despite its presence in other provinces of Ecuador and, at high prevalence, in Colombia. Genotyping results revealed a high degree of diversity for MTBC in Esmeraldas: neither active transmission clusters within this province nor including MTBC strains from Colombia or other provinces of Ecuador were found. Conclusions. Our data suggest that tuberculosis dynamics in this rural and isolated area may be not related with highly transmitted strains like MTBC Lineage-Beijing but could be influenced by other health determinants that favor TB relapse like poverty and poor health system access.Further studies including a larger number of MTBC strains from Esmeraldas are necessary to test this hypothesis.